Editorial Perspective: 'From there to here': adapting child and adolescent mental health interventions for low‐resource settings. (March 2017) - Divan, Gauri
Abstract : The majority of evidence for child and adolescent mental health interventions is generated in high‐income countries. However, the majority of the world's children live in low‐ and middle‐income countries, resulting in a large treatment gap for these disorders. A systematic approach to adapt evidence‐based interventions so as to address cultural and contextual issues will increase an interventions acceptability and reach, allowing us to address these enormous unmet needs.